An elastic organic single crystal with bending and high pressure-induced fluorochromism properties. (September 2022) - Peng, Jiang; Han, Chuchu; Li, Siqi; Cao, Xiumian; Bai, Jiakun; Li, Junfei; Ren, Ying; Wang, Yifan; Wu, Jinnan; Jia, Junhui
Abstract: The mechanically tunable flexible fluorochromic elastic organic single crystals are extremely rare. Fortunately, we prepared a needle-like elastic crystal (TPABA ) with bending and high pressure-induced fluorochromism properties. With the reversible change of hydrostatic pressure, the crystal fluorescence underwent reversible red-shift and blue-shift (wavelength change greater than 100 nm). Interestingly, upon bending, the inner and outer arcs on the (002) and (200) surfaces of the crystal exhibited distinct fluorochromic effects by spatially resolved μ-PL measurements. Upon bending, the fluorescence emission of the inner and outer arcs on the (002) face of the crystal was red-shifted and blue-shifted by 26 nm and 4 nm, respectively. Different from (002) face, the inner arc and outer arc of the crystal (200) plane were only blue-shifted and red-shifted by 2 nm and 3 nm, respectively. Theoretical calculations indicated that, on the one hand, with the reversible bending of the crystal, the intermolecular interaction force distance in the crystal would change reversibly, and the corresponding inner and outer arc fluorescence emission wavelengths of the crystal plane would reversibly change. On the other hand, the number of π-π interactions on each face of the crystal had an important effect on the bending-induced fluorochromism of the crystal. This paper provided new idea for the preparation of the multi-faceted bending fluorochromism flexible crystals. Graphical abstract: Image 1 Highlights: Multi-faceted bending elastic organic single crystals. The elastic crystals exhibit bending and high pressure-induced fluorochromism properties. The inner and outer arcs on the (002) and (200) surfaces of the crystal exhibited distinct fluorochromic effects.